1999
DOI: 10.1177/096368979900800306
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Xenografted Fetal Porcine Pancreatic Tissue is Superior in Inbred Scid (C.B-17/Icr-scid/scid) Compared to Outbred Nude (CD-1-nu/nu) Mice

Abstract: Nude mice are used as recipients of foreign tissue because of their inability to reject these grafts. Our experience has been that there is variable rejection of fetal porcine insulin-producing tissue transplanted into CD-1 (athymic) outbred nude mice. To examine the suitability of this line of nude mouse as a recipient of the tissue, fetal porcine pancreas was grafted either into these outbred animals or into an inbred mutant strain of mice, the more immunocompromised severe combined immunodeficient (scid) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Higher natural killer cell activity was reported in athymic nude mice (33). Differences in the growth rates of normal tissues (34) and inconsistencies in the response to therapies of tumors grown in athymic nude and scid mice have been previously reported (35). Differences in gene expression profiles of tumors grown in athymic nude and scid mice confirm the importance of host immune responses (36).…”
Section: Discussionmentioning
confidence: 69%
“…Higher natural killer cell activity was reported in athymic nude mice (33). Differences in the growth rates of normal tissues (34) and inconsistencies in the response to therapies of tumors grown in athymic nude and scid mice have been previously reported (35). Differences in gene expression profiles of tumors grown in athymic nude and scid mice confirm the importance of host immune responses (36).…”
Section: Discussionmentioning
confidence: 69%
“…They were glycemic male severe combined immunodeficient (SCID) mice, as has been described previously (23). We have washed twice with HEPES-buffered Earle's medium, which consists of 124 mM NaCl, 5.4 mM KCl, 1.8 mM shown that these grafts will normalize blood glucose levels of diabetic recipients 5-8 weeks after being trans-CaCl 2 , 0.8 mM MgSO 4 , 1 mM NaH 2 PO 4 , 14.3 mM NaHCO 3 , and 2 mM glucose supplemented with 0.2% planted (23). In initial experiments the tissue was placed beneath the left renal capsule only, but in later experi-bovine serum albumin (Sigma) and 10 mM HEPES.…”
Section: Immunodeficient Mice Static Stimulation In Vitromentioning
confidence: 99%
“…Glucagon from the α-cells normalizing blood glucose levels when transplanted into and somatostatin from the δ-cells cannot be used bediabetic rodents (9,11,17,23). The time taken to achieve cause the peptide is indistinguishable in the pig and the this goal is 2-4 months during which there is an inrodent.…”
Section: Introductionmentioning
confidence: 99%
“…Uncultured 1-mm 3 fragments of fetal pig pancreas were transplanted beneath the renal capsule of NOD-SCID mice as described previously (6). Uncultured 1-mm 3 fragments of fetal pig pancreas were transplanted beneath the renal capsule of NOD-SCID mice as described previously (6).…”
Section: Transplantation Of Pancreatic Explants Into Nonobese Diabetimentioning
confidence: 99%
“…Insulinproducing fetal pig cells are capable of normalizing blood glucose levels when transplanted into diabetic mice (2)(3)(4)(5)(6) and rats (7). Insulinproducing fetal pig cells are capable of normalizing blood glucose levels when transplanted into diabetic mice (2)(3)(4)(5)(6) and rats (7).…”
mentioning
confidence: 99%